In-situ evaluation of the damaging process of C/SiC composite material bolts under tensile loading - Jianyu Yuan; Zhejun Liu; Jincheng Pang; Ying Wang; Guojun Xie; Xin Lin; Lu Han; Wu Lu; Lin Xu (Composites Part C: Open Access, 2021)
The infrared (IR) thermography and acoustic emission (AE) monitoring are employed to evaluate the damaging process of C/SiC composite material bolts (M10) under tensile loading. The temperature variation over time before and after the breaking moment, as well as the temperature distribution near the fracture are investigated on the basis of real-time temperature evolution results obtained from IR analyzing. Multiple AE parameters including AE hits, duration time and energy are employed for comprehensive investigation on the failure mechanism based on the behavior of the fibers, matrix and the interphase. The results indicate that the IR signal mostly originates from the breaking process (lasting period less than 0.1 s) and localizes at the thread root (∼2 mm around the fracture) on the fixture surface. The histogram of AE activity indicates that the intensity of the crack propagation peaks at the middle stage of the tensile loading process, while the energy abruptly outbreaks at clustered and isolated loading forces, as a result of damage accumulation in the tensile loading process. The IR and AE results fit well with the microstructure of the fracture. The proposed in-situ evaluation method makes it possible to evaluate the real time damaging process and failure mechanism of C/SiC composite material bolts.